Interpreting and reporting fracture classification and operation type in hip fracture: implications for research studies and routine national audits. (October 2019) - Masters, James; Metcalfe, David; Parsons, Nick R.; Achten, Juul; Griffin, Xavier L.; Costa, Matt L.; ,
Abstract : Aims: This study explores data quality in operation type and fracture classification recorded as part of a large research study and a national audit with an independent review. Patients and Methods: At 17 centres, an expert surgeon reviewed a randomly selected subset of cases from their centre with regard to fracture classification using the AO system and type of operation performed. Agreement for these variables was then compared with the data collected during conduct of the World Hip Trauma Evaluation (WHiTE) cohort study. Both types of surgery and fracture classification were collapsed to identify the level of detail of reporting that achieved meaningful agreement. In the National Hip Fracture Database (NHFD), the types of operation and fracture classification were explored to identify the proportion of "highly improbable" combinations. Results: The records were reviewed for 903 cases. Agreement for the subtypes of extracapsular fracture was poor; most centres achieved no better than "fair" agreement. When the classification was collapsed to a single option for "extracapsular" fracture, only four centres failed to have at least "moderate" agreement. There was only "moderate" agreement for the subtypes of intracapsular fracture, which improved to "substantial" when collapsed to "intracapsular". Subtrochanteric fracture types were well reported with "substantial" agreement. There was near "perfect" agreement for internal fixation procedures. "Perfect" or "substantial" agreement was achieved when the type of arthroplasty surgery was reported at the level of "hemiarthroplasty" and "total hip replacement". When reviewing data submitted to the NHFD, a minimum of 5.2% of cases contained "highly improbable" procedures for the stated fracture classification. Conclusion: The complexity of collecting fracture classification data at a national scale compromises the accuracy with which detailed classification systems can be reported. Data around type of surgery performed show similar tendencies. Data capture, reporting, and interpretation in future studies must take this into account. Cite this article: Bone Joint J 2019;101-B:1292–1299